STRATEGI GURU DALAM MENGATASI KEJENUHAN PESERTA DIDIK PADA PROSES PEMBELAJARAN PAI DI SDN 7 BANAWA SELATAN - Nur Salsabila, Nur Salsabila; Suharnis; Firdiansyah Alhabsyi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
(1)Several factors contribute to students' boredom in the Islamic Religious Education (PAI) learning process in Grade IV at SDN 7 Banawa Selatan, including the lack of variation in teaching methods, the learning process being confined to the classroom, an unchanging learning environment, and prolonged mental tension during lessons. (2) The strategies employed by teachers to overcome student boredom in the PAI learning process in Grade IV at SDN 7 Banawa Selatan include direct instruction strategies, indirect instruction strategies, interactive instruction strategies, and independent learning strategies.